Model Prioritisasi Penanganan Jalan Kota Jambi Berbasis Metode Analytical Hierarchy Process - Judhono, M Agung Prasetyo; Sjafruddin, Ade; Wibowo, Sony Sulaksono (Universitas Batanghari Jambi, 2025)
Road maintenance, as an effort to maintain its performance, plays a crucial role in a road network management system. However, insufficient resources and differences in how stakholders perceive this issue pose challenges in the process of programming road maintenance. This study aims to develop a road maintenance prioritization model based on the Analytical Hierarchy Process (AHP) for the road network under the authority of the Jambi City Government. The AHP-based weighting is conducted based on a hierarchical decision-making model for road maintenance, which consists of three main criteria: technical road conditions, socio-economic factors, and connectivity, along with their respective sub-criteria. The results of the study show that in the main criterion, road technical conditions weighted the highest of all with a value of 0,65. Followed by connectivity at 0,19 and socio-economic at 0,16. Then regarding the sub-criterion, the highest global weight is road damage level, with a value of 0,28. The model developed in this study is expected to be used as a decision-making support tools to program road maintenance. The multi-criteria assesment which was conducted is expected to evaluate road priority level holistically and provide a new perspective in decision-making.